Female Characters in Doctor Zhivago and Their Role in the Fate of the Protagonist - Nure Jannat (Transbaikal State University, 2021)
The article attempts to compare the three female characters in the novel Doctor Zhivago to identify their role in the formation of the psychological image of the main character, as well as their main functions as characters in the plot structure of the novel. Distinguishing the terms “character” and “hero” as theoretical concepts, we seek to establish the complementarity of two methods: character analysis as a way of structuring the text, on the one hand, and phenomenological, which allows us to capture the uniqueness of a single hero, as well as its influence on the fate of other participants in the action. Taking into account the long-term work on Doctor Zhivago, the author of the article proceeds from the idea that along with autobiographical material in the characterization of three women – Tonya, Larisa, and Marina, B. Pasternak widely uses plot analogies with masterpieces of Russian and world literature, as well as certain allusions to biblical images. Important here is the principle of inseparability and non-confusion in the depiction of the fates of the three women in their relationship with the main character, associated with the Christian tradition. For the first time, the article introduces the essentiality– existentiality opposition to compare the main female figures. At the same time, it is important that the author, creating female images, uses a different measure of fabulousness associated with the vicissitudes in the life of the main character – the maximum in the relationship of Yuri and Lara and the minimum in relation to the hero with Marina. There is also a different degree of detail of the three images, the use of symbols in their characterization, and the symbolization as the main method of Marina’s characterization is noted. The author concludes that the outstanding Russian poet and novelist B. Pasternak shows a high degree of skill, penetrating the depths of female psychology. At the same time, while maintaining the principles of construction characteristic of the classical narrative, the writer, thanks to the special arrangement of the material, gives the novel features that bring it closer to the best examples of world literature of the twentieth century.